Adverse effect of Mn doping on the magnetic ordering in Mn doped TiO2 nanoparticles. (7th September 2015) - Choudhury, Biswajit; Paul, Susmita; Ameen Ahmed, Gazi; Choudhury, Amarjyoti
Abstract: Herein, we have examined the role played by non-magnetic Mn on the magnetic properties of TiO2 nanoparticles. The samples display complete paramagnetic behavior at room temperature as well as at 10 K. Paramagnetism might be associated with the presence of isolated magnetic spins of Mn 2+ in the system. Observation of negative Curie–Weiss temperature indicates presence of antiferromagnetic interaction in the system. Direct exchange interaction of Mn 2+ –Mn 2+ and antiferromagnetic superexchange interaction of Mn 2+ ions via lattice O 2− ions contribute to antiferromagnetism. Surprisingly, ferromagnetism appears in pure and Mn doped (0.07 mol) TiO2 nanoparticles on vacuum calcination. Although Mn doped TiO2 displays ferromagnetism, there is a loss in magnetization as compared to the undoped TiO2 . It is speculated that low growth temperature during vacuum calcinations might have resulted in amorphous MnO phase separation. This could result in competing ferromagnetic–antiferromagnetic interactions and overall reduction in magnetization. From the results it is evident that TiO2 could be made ferromagnetic by introducing sufficient concentration of oxygen vacancies in the system. Mn doping, however, has an adverse effect on the overall ferromagnetic ordering, as there is possibility of antiferromagnetic d–d exchange interaction of Mn 2+ ions as well as possibility of antiferromagnetic manganese oxide phases separation.